Sharpening of non-recursive comb decimation structure - Cruz Jimenez, Miriam Guadalupe; Calderon Reyes, Vanessa; Jovanovic Dolecek, Gordana (2013 13th International Symposium on Communications and Information Technologies (ISCIT), 2013)
This paper proposes the application of the improved sharpening technique to a non-recursive comb decimation filter, where the decimation factor M is a power of two. The goal is to improve simultaneously the Worst-Case Passband (WCP) and Worst-Case Attenuation (WCA). The coefficients of the sharpening polynomials are expressed as Sum of Power of Two (SPT), leading to a multiplierless structure with a non-significant increase of amount of Additions Per Output Sample (APOS). The resulting filter has a higher attenuation in its first folding band (where the worst-case attenuation occurs) and a droop-compensated passband. Included examples prove the efficiency of the method.